Indigenous Knowledge Preservation Through Integration of Modern Technologies in Public Libraries in Akwa Ibom State, Nigeria - Udoh, Inemesit; Ugwulebo, Jeremiah; Ekpenyong, Glory (Brawijaya University Library, 2026)
Indigenous knowledge preservation is a global preoccupation and the integration of modern technologies is of great prominence. The study examined indigenous knowledge preservation through integration of modern technologies in public libraries in Akwa Ibom State, Nigeria. It adopted mixed methods research of quantitative and qualitative types, with a population of 57 library staff. The total enumeration sampling technique was used since the study population was small and manageable. Data were collected using the researchers’ developed questionnaire, unstructured interview and observation methods. Data collected were analysed quantitatively using descriptive statistics of frequency count, mean scores and standard deviation, as well as qualitatively to validate the results of the quantitative analyses. The study revealed that public libraries in Akwa Ibom State play crucial roles in the preservation of indigenous knowledge by collecting, documenting, classifying and securing indigenous knowledge resources, while collaborating with indigenous communities for the sustenance of indigenous knowledge systems. It indicated that though the overall extent to which modern technologies are integrated for indigenous knowledge preservation in public libraries in Akwa Ibom State, is quite low, but integrating modern technologies can greatly facilitate easy communication between indigenous peoples, security of indigenous knowledge materials against theft, speedy access to indigenous knowledge assets devoid of geographical barrier, among others. The study identified financial challenges, technical/skill-related constraints, manpower constraints, and socio-cultural/policy-related constraints as the four cardinal issues hampering integration of modern technologies in indigenous knowledge preservation. It recommended, among other measures, that government of Akwa Ibom State should provide adequate funding to public libraries to acquire and maintain modern technologies for indigenous knowledge preservation, while staff in the public libraries should be regularly trained on emerging technologies, skill requirements and techniques of enhancing effective use of modern technologies for indigenous knowledge preservation in the public libraries, Nigeria.